A MINIMAL-INVASIVE METHOD TO RETRIEVE AND IDENTIFY ENTHESEAL TISSUE FROM PSORIATIC ARTHRITIS PATIENTS - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Soare, A.; Bräuer, Lars; Rech, Jürgen; Simon, David; Kleyer, Arnd; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

CD200+ fibroblasts form a pro-resolving mesenchymal network in arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Soare, Alina; Treutlein, Christoph; Kemble, Samuel; Mahony, Christopher B.; Geisthoff, Manuel; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Xu, Cong; et al. (Nature Immunology, 2024)
Fibroblasts are important regulators of inflammation, but whether fibroblasts change phenotype during resolution of inflammation is not clear. Here we use positron emission tomography to detect fibroblast activation protein (FAP) as a means to visualize fibroblast activation in vivo during inflammation in humans. While tracer accumulation is high in active arthritis, it decreases after tumor necrosis factor and interleukin-17A inhibition. Biopsy-based single-cell RNA-sequencing analyses in experimental arthritis show that FAP signal reduction reflects a phenotypic switch from pro-inflammatory MMP3+/IL6+ fibroblasts (high FAP internalization) to pro-resolving CD200+DKK3+ fibroblasts (low FAP internalization). Spatial transcriptomics of human joints indicates that pro-resolving niches of CD200+DKK3+ fibroblasts cluster with type 2 innate lymphoid cells, whereas MMP3+/IL6+ fibroblasts colocalize with inflammatory immune cells. CD200+DKK3+ fibroblasts stabilized the type 2 innate lymphoid cell phenotype and induced resolution of arthritis via CD200–CD200R1 signaling. Taken together, these data suggest a dynamic molecular regulation of the mesenchymal compartment during resolution of inflammation.
Created from Fastlane, Scopus look-up

Concise report: a minimal-invasive method to retrieve and identify entheseal tissue from psoriatic arthritis patients - Pachowsky, Milena; Raimondo, Maria Gabriella; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (Annals of the Rheumatic Diseases, 2022)
Objectives To establish a minimally invasive biopsy technique for the analysis of entheseal tissue in patients with psoriatic arthritis (PsA). Methods Human cadavers were used for establishing the technique to retrieve tissue from the lateral humeral epicondyle enthesis (cadaveric biopsies). After biopsy, the entire enthesis was surgically resected (cadaveric resections). Biopsies and resections were assessed by label-free second harmonic generation (SHG) microscopy. The same technique was then applied in patients with PsA with definition of entheseal tissue by SHG, staining of CD45+immune cells and RNA extraction. Results Entheseal biopsies from five cadavers allowed the retrieval of entheseal tissue as validated by the analysis of resection material. Microscopy of biopsy and resection sections allowed differentiation of entheseal, tendon and muscle tissue by SHG and definition of specific intensity thresholds for entheseal tissue. In subsequent entheseal biopsies of 10 PsA patients: the fraction of entheseal tissue was high (65%) and comparable to cadaveric biopsies (68%) as assessed by SHG microscopy. Furthermore, PsA biopsies showed immune cell infiltration and sufficient retrieval of RNA for further molecular analysis. Conclusion Entheseal biopsy of the lateral epicondyle is feasible in patients with PsA allowing reliable retrieval of entheseal tissue and its identification by SHG microscopy.
CRIS-Team WoS Importer:2022-05-13

Entheseal Biopsy Approach: An Ultrasound-guided Method for Retrieval of Entheseal Tissue from Psoriatic Arthritis Patients - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

TEMPORAL MIGRATION OF IMMUNE CELLS FROM PSORIATIC SKIN TO JOINTS INITIATING SYNOVIAL INFLAMMATION IN PSORIATIC ARTHRITIS - Raimondo, Maria Gabriella; Rauber, Simon; Xu, Cong; Mohammadian, Hashem; Vogg, Mario; Anchang, Charles Gwellem; Rigau, Aleix; Luber, M.; Labinsky, Hannah; Soare, A.; Distler, Jörg; Fearon, U.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

The potential of omics technologies for the treatment of immune‐mediated inflammatory diseases - Anchang, Charles Gwellem; Xu, Cong; Raimondo, Maria Gabriella; Atreya, Raja; Maier, Andreas; Schett, Georg; Zaburdaev, Vasily; Rauber, Simon; Ramming, Andreas (International Journal of Molecular Sciences, 2021)
Immune‐mediated inflammatory diseases (IMIDs), such as inflammatory bowel diseases and inflammatory arthritis (e.g., rheumatoid arthritis, psoriatic arthritis), are marked by increasing worldwide incidence rates. Apart from irreversible damage of the affected tissue, the systemic nature of these diseases heightens the incidence of cardiovascular insults and colitis‐associated neo-plasia. Only 40–60% of patients respond to currently used standard‐of‐care immunotherapies. In addition to this limited long‐term effectiveness, all current therapies have to be given on a lifelong basis as they are unable to specifically reprogram the inflammatory process and thus achieve a true cure of the disease. On the other hand, the development of various OMICs technologies is consid-ered as “the great hope” for improving the treatment of IMIDs. This review sheds light on the pro-gressive development and the numerous approaches from basic science that gradually lead to the transfer from “bench to bedside” and the implementation into general patient care procedures.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Advanced imaging technologies; Immune‐mediated inflammatory diseases (IMIDs); Single‐cell RNA sequencing; Spatial sequencing